Building an interactive program based on e-learning and its impact on the scientific trends of second intermediate students Biology (Journal of the College of Basic Education, 2022)
The objective of the current research is to know the effect of building an interactive program based on e-learning on the scientific attitudes of the second intermediate students of biology, by verifying the following null hypothesis:- There is no statistically significant difference at the level (0.05) between the mean scores of the students of the experimental group who study according to the interactive program based on e-learning and the average scores of the students of the control group who study according to the usual method in the scientific attitudes scale.The experimental design with partial control was chosen for the two groups (experimental and control), which partially control each other.